Aprendizagem de posturas em equoterapia por crianças com transtorno do espectro autista (TEA) - Barbosa, Gardenia de Oliveira (Universidade Federal de São Carlos, 2016)
The autistic spectrum disorder (ASD) is characterized by inadequacies in social interaction, communication skills, learning and adaptability. The person with ASD should be exposed to conditions that stimulate its maximum development in order to promote the learning process in different contexts. In this sense, the hippotherapy can be an effective strategy in the child development process with ASD, since it favors different sensory systems. However, in order the learning process to become efficient, it is necessary to employ compensatory teaching strategies that provide access to information in order to provide effective opportunity to participate in the activity. The study aimed at analyzing the effectiveness of aid levels in the posture learning process in hippotherapy for children with ASD. As for the method, this study was single-subject design, type AB with replicas of designs with single subject; three children with ASD aged between four and nine years had participated in the study. Participants underwent hippotherapy intervention lasting four months, twice a week, corresponding to 31 individual sessions of hippotherapy. As data collection instrument was made anamnesis with the parents or guardians, the Assessment of Basic Learning Abilities, field diary and checklist. The checklist was based on 10 postures namely, mount, prone, side mount, inverted mount, inverted prone, standing in the stirrups, four supports, inverted four supports, kneeling and reversed kneeling. The data analysis on the progress of each participant was descriptive. Regarding the results, it was observed that all participants were able to perform the postures with verbal assistance at the late intervention, and the learning process mediated by the visualverbal, physical and verbal aids. The latter was predominant. We conclude that the aid was effective overall, once all participants have evolved compared to the baseline, they also respond more effectively to physical and verbal assistance to later the verbal one. Moreover, learning is favored by the association of various aids, as different sensory inputs were benefited; therefore, there is no universally more efficient method; each child has a peculiar way of relating to the world and hence to the learning processes.
Keywords: Educação especial; Equoterapia; Autismo; Transtorno do espectro autista (TEA); Aprendizagem; Special education; Hippotherapy; Autism; Autistic spectrum disorder (ASD); Learning; CIENCIAS HUMANAS::EDUCACAO